2018
DOI: 10.18203/2320-6012.ijrms20184442
|View full text |Cite
|
Sign up to set email alerts
|

Study of brainstem auditory evoked potentials in early (grade I) essential hypertensive patients

Abstract: Background: Essential hypertension is one of the most common world’s health diseases. It   frequently affects central nervous system (CNS) by producing micro-infarctions which results into altered evoked potentials. Previous studies have shown correlation between hypertension and brain stem auditory evoked potentials. But very scarce data is available on all the parameters of BAEP and essential hypertension especially “amplitude ratio” which distinguishes between central and peripheral impairment. This study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Tandon et al 10 also failed to find significant differences in IWIs between hypertensives and controls. In contrast, Gawali et al 12 reported significantly shorter IWI I–III in hypertensives than controls. In our study, the only significant difference in IWIs between optimal and nonoptimal BP subjects was IWI III–V at the highest stimulus level, which was 0.14 milliseconds longer in the nonoptimal BP group.…”
Section: Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…Tandon et al 10 also failed to find significant differences in IWIs between hypertensives and controls. In contrast, Gawali et al 12 reported significantly shorter IWI I–III in hypertensives than controls. In our study, the only significant difference in IWIs between optimal and nonoptimal BP subjects was IWI III–V at the highest stimulus level, which was 0.14 milliseconds longer in the nonoptimal BP group.…”
Section: Discussionmentioning
confidence: 84%
“…In our study, the only significant difference in IWIs between optimal and nonoptimal BP subjects was IWI III–V at the highest stimulus level, which was 0.14 milliseconds longer in the nonoptimal BP group. Prolonged IWI III–V has been identified in some, 11 12 but not all 10 other related ABR studies in HTN. To evaluate the potential contribution of hearing sensitivity to absolute wave latencies and IWIs, we included PTA 1,2,3,4 as a covariate in the linear mixed effects model.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations